Jezik in kultura v raziskovanju medetničnih odnosov - predstavitev izbranih vidikov - Novak-Lukanovič, Sonja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
LANGUAGE AND CULTURE IN THE RESEARCH OF INTERETHNIC RELATIONS - PRESENTATION OF SELECTED ASPECTS. The article presents selected research projects which have been taking place within the framework of the Institute for Ethnic Studies programme. These projects, as to their contents and metho dology, were dedicated to the field of language and culture in interethnic relations. The article exposes topics which have been researched by the author, i.e. linguistic and cultural pluralism, language accomodation, economic aspects of language. Special attention is dedicated to the OECD/CERI project Education, Cultural and Linguistic Pluralism , and to selected empirical data of language accomodation, arising from the yearlong longitudinally schemed project Ethnic Identity and Interethnic Relations in the Slovene Ethnic Territory; also presented are the Alps/Adriatic project on the status of minorities within this regional territory, the Unesco project on multi-layer identity, and the research study carried out within the Target Research Project Perception of Linguistic and Cultural Diversity in Border Towns.
Keywords: culture; kultura; regionalizem; medetnični odnosi; raziskovalni projekti; jezikovni pluralizem